2011
DOI: 10.1111/j.1369-7625.2011.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Managing patient involvement’: provider perspectives on diabetes decision‐making

Abstract: Background Most studies of shared decision-making focus on acute treatment or screening decision-making encounters, yet a significant proportion of primary care is concerned with managing patients with chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Findings have shown that the main motive for health professionals to initiate user involvement is to gain access to user knowledge as an alternative to professional knowledge or as support for professional knowledge (Sahlsten, Larsson, Sjöström, & Plos, 2009; Solbjør & Steinsbekk, 2011). However, the responsibility to deliver evidence-based or high-quality care, together with respecting service users’ right to make decisions, is sometimes described as conflicting (Shortus, Kemp, McKenzie, & Harris, 2013; Solbjør & Steinsbekk, 2011). Ensuring high-quality care is described as an argument for limiting user involvement and for professionals to decide and to exert control over patient care (Larsson, Liljedahl, & Gard, 2010; Shortus et al, 2013; Solbjør & Steinsbekk, 2011; Tobiano, Bucknall, Marshall, Guinane, & Chaboyer, 2015; Tobiano, Marshall, Bucknall, & Chaboyer, 2016), valuing professional knowledge above user knowledge (Solbjør & Steinsbekk, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings have shown that the main motive for health professionals to initiate user involvement is to gain access to user knowledge as an alternative to professional knowledge or as support for professional knowledge (Sahlsten, Larsson, Sjöström, & Plos, 2009; Solbjør & Steinsbekk, 2011). However, the responsibility to deliver evidence-based or high-quality care, together with respecting service users’ right to make decisions, is sometimes described as conflicting (Shortus, Kemp, McKenzie, & Harris, 2013; Solbjør & Steinsbekk, 2011). Ensuring high-quality care is described as an argument for limiting user involvement and for professionals to decide and to exert control over patient care (Larsson, Liljedahl, & Gard, 2010; Shortus et al, 2013; Solbjør & Steinsbekk, 2011; Tobiano, Bucknall, Marshall, Guinane, & Chaboyer, 2015; Tobiano, Marshall, Bucknall, & Chaboyer, 2016), valuing professional knowledge above user knowledge (Solbjør & Steinsbekk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the responsibility to deliver evidence-based or high-quality care, together with respecting service users’ right to make decisions, is sometimes described as conflicting (Shortus, Kemp, McKenzie, & Harris, 2013; Solbjør & Steinsbekk, 2011). Ensuring high-quality care is described as an argument for limiting user involvement and for professionals to decide and to exert control over patient care (Larsson, Liljedahl, & Gard, 2010; Shortus et al, 2013; Solbjør & Steinsbekk, 2011; Tobiano, Bucknall, Marshall, Guinane, & Chaboyer, 2015; Tobiano, Marshall, Bucknall, & Chaboyer, 2016), valuing professional knowledge above user knowledge (Solbjør & Steinsbekk, 2011). Although actively involved patients were considered valuable to enrich the professionals’ work, it is also looked upon as time-consuming and increasing the workload (Arnetz, Winblad, Arnetz, & Höglund, 2008; Arnetz & Zhdanova, 2015; Solbjør & Steinsbekk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Providers need to understand the potential influence of cultural factors on DSM so that they can provide culturally competent DSM education in a context that promotes patient understanding and adherence (2). However, the literature is limited on the role of culture in DSM from the providers’ perspective (36), and is even more limited with regard to Arab Americans specifically.…”
mentioning
confidence: 99%
“…Proper education is central to effective DSM, and health care providers play a primary role in providing this education (5,6,11). Providers must pay special attention to cultural competence because different cultures view diabetes, and hence DSM, in different ways.…”
mentioning
confidence: 99%
“…These low summed involvement scores likely indicate that patients are “generally not” or only “sometimes” involved in their health care relating to a particular medical condition. Most of the existing literature on this topic is more qualitative in nature and studied individual patient’s preferences with the patient’s involvement in care and effectiveness of specific techniques 2325. This is an important finding because now that we know that patients are not very involved in their health care, we can further study how this lack of involvement affects quality of care, health outcomes, and patient safety.…”
Section: Discussionmentioning
confidence: 99%